2004
DOI: 10.1016/s0264-9993(02)00086-x
|View full text |Cite
|
Sign up to set email alerts
|

Projecting world food demand using alternative demand systems

Abstract: Computable General Equilibrium (CGE) models are increasingly being used to project world food markets in order to support forward-looking policy analysis. Such projections hinge critically on the underlying functional form for representing consumer demand. Simple functional forms can lead to unrealistic projections by failing to capture changes in income elasticities of demand. We adopt as our benchmark the recently introduced AIDADS demand system and compare it with several alternative demand systems currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…Yu et al (2004) indicate that the Rotterdam model (Barten 1964;Theil, 1965) has become a prominent vehicle for the econometric analysis of patterns of consumer demand and rigorous testing of the utility maximisation theory. Barnett and Seck (2008) point out that the Rotterdam model gained prominence in food demand analysis, thanks to its locally flexible functional form.…”
Section: Orange Import Allocation Modelmentioning
confidence: 99%
“…Yu et al (2004) indicate that the Rotterdam model (Barten 1964;Theil, 1965) has become a prominent vehicle for the econometric analysis of patterns of consumer demand and rigorous testing of the utility maximisation theory. Barnett and Seck (2008) point out that the Rotterdam model gained prominence in food demand analysis, thanks to its locally flexible functional form.…”
Section: Orange Import Allocation Modelmentioning
confidence: 99%
“…AIDADS is a demand system which allows the marginal budget shares to vary as a function of total expenditure. Recent work by Yu et al (2004) has demonstrated the superiority of AIDADS over other demand systems in projecting food demand, especially for long-term projections involving a wide range of countries.…”
Section: The Modelmentioning
confidence: 99%
“…The parameters q and q de…ning the varying marginal budget shares of goods and services q in the consumers' total real expenditures in equation (39) are estimated by maximum likelihood as described in Cran…eld et al (2003) and Yu et al (2004). The parameters q de…ne the subsistence level of consumption 1 4 Note that the minimum age parameter, v, is not included in equation (49).…”
Section: Preferences and Welfarementioning
confidence: 99%